2019
DOI: 10.1055/a-0820-3584
|View full text |Cite
|
Sign up to set email alerts
|

Geschlechterspezifische Inanspruchnahme von Gesundheitsleistungen in einer urbanen Erwachsenenpopulation

Abstract: Zusammenfassung Ziel der Studie Ziel der Studie ist es, Ergebnisse zur geschlechterspezifischen Inanspruchnahme von Gesundheitsleistungen in einer urbanen Erwachsenenpopulation bereitzustellen. Methoden Im Zuge der LIFE-ADULT-Studie wurden 2244 Erwachsene (19–79 Jahre) zum Inanspruchnahmeverhalten von Gesundheitsleistungen innerhalb des letzten Jahres befragt. Die Angaben zu Haus- und Facharztkonsultation, hausärztliche Beratung sowie Inanspruchnahme präventiver- bzw. gesundheitsfördernder Maßnahmen wurden aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
0
12
0
3
Order By: Relevance
“…There may also be a pattern of overuse, unjustified from a medical point of view, related to the clinical condition, frequency, intensity, or sophistication of the service that does not compensate for the benefit. This overuse is based on multiple causes [ 20 , 21 , 22 ], such as self-perception of loss of health or well-being, symptoms, type of disease, time of disability, as well as the patient’s perception of biological or social restriction to develop daily activities [ 20 , 23 , 24 ]. The wish for care also depends on beliefs on health, tolerance of discomfort, and trust in the health care system [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There may also be a pattern of overuse, unjustified from a medical point of view, related to the clinical condition, frequency, intensity, or sophistication of the service that does not compensate for the benefit. This overuse is based on multiple causes [ 20 , 21 , 22 ], such as self-perception of loss of health or well-being, symptoms, type of disease, time of disability, as well as the patient’s perception of biological or social restriction to develop daily activities [ 20 , 23 , 24 ]. The wish for care also depends on beliefs on health, tolerance of discomfort, and trust in the health care system [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Colombian health service users ( n = 11,121,054) were assessed in 2017 by means of clinical records and showed that women used health services more than men [ 23 ]. The assessment of 2244 German 19–79-year-old patients in 2020 reported that women visited doctors and used health prevention and promotion programs more often than men [ 24 ]. This fact may be due to various factors such as greater early identification of symptoms, biological differences, greater perception of the disease, and cultural aspects.…”
Section: Discussionmentioning
confidence: 99%
“…However, two smaller studies documented an almost fourfold (32.8%) [19] and sevenfold (48%) [17] prevalence of counseling, respectively, in older patients. In a sub-sample of the Leipzig Life Study, 21.5% of patients reported having received PA counseling from their primary care physician [22].…”
Section: Prevalence Of Counselingmentioning
confidence: 99%
“…Studies have identified many reasons why rates of diagnosis and treatment are lower in men ( Warren, 1983 ; Fava et al, 1991 ; Spence and Robbins, 1992 ; Courtenay, 2000 ; Möller-Leimkühler, 2000 , 2002 , 2016 ; Swendsen and Merikangas, 2000 ; Möller-Leimkühler et al, 2002 ; Zierau et al, 2002 ; Cochran and Rabinowitz, 2003 ; Yu et al, 2004 ; Berger et al, 2005 ; Brownhill et al, 2005 ; Kessler et al, 2005 ; Sigmon et al, 2005 ; Winkler et al, 2005 ; Emslie et al, 2006 ; Rutz and Rhimer, 2007 ; Davis et al, 2008 ; Hausmann et al, 2008 ; Magovcevic and Addis, 2008 ; Oliffe and Phillips, 2008 ; Chuick et al, 2009 ; Cohn et al, 2009 , 2010 ; Levant et al, 2009 , 2011 , 2013 ; Rochlen et al, 2010 ; Weaver et al, 2010 ; Martin et al, 2011 , 2013 ; McCusker and Galupo, 2011 ; Oliffe et al, 2011 , 2012 , 2013 ; Rice et al, 2013 ; Lai et al, 2015 ; Yousaf et al, 2015 ; Whittle et al, 2015 ; Seidler et al, 2016 ; Cavanagh et al, 2017 ; Reiß, 2017 ; Rommel et al, 2017 ; Braly et al, 2018 ; Keil et al, 2020 ; Serafini et al, 2016 , 2017 ). For example, men use medical services and preventive and health-promoting measures far less often than women ( Seidler et al, 2016 ; Rommel et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%